(untitled) (Journal of Innovative Counseling : Theory, Practice, and Research, 2024)
The purpose of this study was to find an overview of online game addiction and the effectiveness of a hypnosis-oriented counseling approach to online gaming behavior in class XII students of SMK Negeri 1 Tasikmalaya. This type of research is quantitative research with purposive sampling using A-B or baseline-intervention single subject design. The population of class XII students amounted to 564 people with a sample of 247 people and students who were categorized as moderate and severe in female and male students were taken. The data analysis technique used used a Likert scale and categorization. The result of this study is that hypnosis- oriented counseling is very effective in reducing online game addiction with the male quadratic regression trend (R2 = 0.08812) while the female quadratic regression trend (R2 = 0.9315).